2014
DOI: 10.19026/rjaset.7.465
|View full text |Cite
|
Sign up to set email alerts
|

Audit Quality and Firm Value: A Case of Pakistan

Abstract: The present study intends to explore the influence of audit committee characteristics on a firm's financial performance. The corporate governance mechanisms are highly recognized in era of global financial crisis and current economic recession. Audit committee is one of the core mechanisms that ensure good corporate governance in the firms. Yet, very less evidence found on the impact of audit committee and its characteristics on firm's performance in the context of Pakistani literature. For that reason, four a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
42
3
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 37 publications
7
42
3
2
Order By: Relevance
“…The results of this study are in line with research conducted by Gill and Obradovich (2012), Fauzi and Locke (2012) and Afza and Nazir (2014) which found positive and significant results between audit committees and firm values.…”
Section: H2: the Audit Committee Has A Positive Effect On Corporate Vsupporting
confidence: 92%
See 2 more Smart Citations
“…The results of this study are in line with research conducted by Gill and Obradovich (2012), Fauzi and Locke (2012) and Afza and Nazir (2014) which found positive and significant results between audit committees and firm values.…”
Section: H2: the Audit Committee Has A Positive Effect On Corporate Vsupporting
confidence: 92%
“…Based on the premise of resource dependence theory, the company's performance will be better as the size of the audit committee (Al-Matar, et.al., 2014) increases. Can be explained as the number of audit committees increases then the market will see that more qualified resources and experts to solve accounting and financial problems are owned by the audit committee (Afza and Nazir, 2014). Similar research conducted by Gill and Obradovich (2012); Afza and Nasir (2014); Al Matar, et.al (2014) who found a positive influence between audit committee and firm value.…”
Section: H1: the Board Of Directors Has A Positive Effect Firm Valuesupporting
confidence: 53%
See 1 more Smart Citation
“…Based on the statistical results, only hypothesis 2 is accepted while other hypotheses are rejected. This result is in line with Afza & Nazir's [16] research which found that investors reacted positively to the high quality of audits in the preparation of financial statements, on the contrary that investors reacted negatively to the low quality of audits because they were related to the low quality of information published in financial statements including performance corporate finance.…”
Section: Goodfit Analysissupporting
confidence: 88%
“…Quality audits, especially those carried out by independent parties, make financial reports reliable, because they are free from the interests of Management [15]. The characteristics of the audit committee have a positive effect on firm value significantly [16]. In relation to the preparation of financial statements, auditors who are reliable in the audit process will carry out their audit functions properly so that opinions are generated objectively and can strengthen investor confidence in the company's financial statements.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%